3-D volumetric MRI evaluation of the placenta in fetuses with complex congenital heart disease. Issue 9 (September 2015) - Andescavage, Nickie; Yarish, Alexa; Donofrio, Mary; Bulas, Dorothy; Evangelou, Iordanis; Vezina, Gilbert; McCarter, Robert; duPlessis, Adre; Limperopoulos, Catherine
Abstract Introduction Placental insufficiency remains a common cause of perinatal mortality and neurodevelopmental morbidity. Congenital heart disease (CHD) in the fetus and its relationship to placental function is unknown. This study explores placental health and its relationship to neonatal outcomes by comparing placental volumes in healthy pregnancies and pregnancies complicated by CHD using in vivo three-dimensional MRI studies. Methods In a prospective observational study, pregnant women greater than 18 weeks gestation with normal pregnancies or pregnancies complicated by CHD were recruited and underwent fetal MR imaging. The placenta was manually outlined and the volume was calculated in cm3. Brain volume was also calculated and clinical data were also collected. Relationships, including interactive effects, between placental and fetal growth, including brain growth, were evaluated using longitudinal multiple linear regression analysis. Results 135 women underwent fetal MRI between 18 and 39 weeks gestation (mean 31.6 ± 4.4). Placental volume increased exponentially with gestational age (p = 0.041). Placental volume was positively associated with birth weight (p < 0.001) and increased more steeply with birth weight in CHD-affected fetuses (p = 0.046). Total brain and cerebral volumes were smaller in the CHD group (p < 0.001), but brainstem volume (p < 0.001) was larger. Placental volumes were not associated with brain volumes. Discussion Impaired placental growth in CHD is associated with gestational age and birth weight at delivery. Abnormalities in placental development may contribute to the significant morbidity in this high-risk population. Assessment of placental volume by MRI allows for in vivo assessments of placental development.